2022
DOI: 10.1159/000525758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Appendicular Muscle Mass in Sarcopenia in Older Adults Using Ultrasonography: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> The measurement of appendicular muscle mass is essential for the diagnosis of sarcopenia. Ultrasonography is an accurate and convenient method used to evaluate muscle mass. <b><i>Objective:</i></b> The aim of the study was to evaluate the diagnostic value of ultrasonography for appendicular muscle mass in sarcopenia in older adults and find out proper ultrasound parameters. <b><i>Methods:</i></b> Medline, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 78 publications
0
17
0
1
Order By: Relevance
“…It was reported that ultrasonography evaluation validated the quantitative assessment of appendicular skeletal muscle mass in older adults. 42 To the best of our knowledge, this is the first study to demonstrate that MT can determine skeletal muscle mass better and conveniently than ASMI.…”
Section: Discussionmentioning
confidence: 84%
“…It was reported that ultrasonography evaluation validated the quantitative assessment of appendicular skeletal muscle mass in older adults. 42 To the best of our knowledge, this is the first study to demonstrate that MT can determine skeletal muscle mass better and conveniently than ASMI.…”
Section: Discussionmentioning
confidence: 84%
“…However, the clinical use of US is narrow due to the lack of a standardized protocol and validated cutoff points. Several new ultrasonic techniques for diagnosing muscle diseases have emerged in recent years, such as elastosonography and artificial intelligence ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is important to highlight that this study makes an important advance in scientific knowledge with the implementation of a training/qualification program for health professionals with different backgrounds. Studies have requested that training programs should be structured to enhance the reliability of US muscle assessment, as there is still no training program or standardized protocols for training health professionals and students [8,19,20,29,30]. In addition, it is also suggested that studies should report data regarding reliability and training, not considering that these are already established in the literature [20].…”
Section: Discussionmentioning
confidence: 99%